Transsternal and Transpericardial Approach to Descending Thoracic Aorta via Median Sternotomy—An Option for Extensive Aortic Surgery - Park, Kay-Hyun (AORTA, 2022)
We describe a technique for approaching the distal descending thoracic aorta via median sternotomy and posterior pericardiotomy, which enabled us to perform the extensive aortic repair. While this approach shared the lesser invasiveness of the frozen elephant trunk procedure with less confinement by anatomic features, the advantage was counterbalanced by the high incidence of spinal cord ischemia. This approach can be an option in highly selected patients who require extensive aortic repair but have factors prohibiting other conventional approaches.
Keywords: elephant trunk; frozen elephant trunk; chronic dissection; extensive aneurysm